2012
DOI: 10.1007/s11136-012-0148-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, reliability and validity of the Chinese simplified version of the MOS-HIV health survey among AIDS patients in China

Abstract: The Chinese simplified version of MOS-HIV health survey had good feasibility, reliability and validity. It was successfully adapted for AIDS patients in rural areas and could be a valuable tool in evaluating the quality of life of AIDS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…In addition, an excellent success rate was also demonstrated by the results of the item-discriminant validity tests. Our results showed that the convergent validity and discriminant validity measures for all scales were satisfactory, representing findings that were consistent with those of previous studies [ 6 , 35 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, an excellent success rate was also demonstrated by the results of the item-discriminant validity tests. Our results showed that the convergent validity and discriminant validity measures for all scales were satisfactory, representing findings that were consistent with those of previous studies [ 6 , 35 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…In light of distribution of the MOS-HIV scores, three scales (role function (35.4%), social function (17.8%), and cognitive function (15.7%)) showed moderate ceiling effects; similar effects have been previously reported [ 6 , 37 39 ]. This phenomenon could be in part attributable to the presence of fewer items in the role function, social function, and cognitive function domains [ 6 , 37 39 ]. The observed ceiling effects may also imply that these scales have weak differentiation capabilities; however, the internal consistency tests confirmed that the items were more highly correlated with their own scales than with others.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It also permits within-group and cross-cultural comparisons as it has been applied to PLWHA worldwide, enabling the use of a vast amount of accumulated data for such comparisons [ 13 ]. The feasibility of the use of the MOS-HIV has been proven [ 14 , 15 ], and it has been validated in several languages such as Chinese [ 16 , 17 ], French [ 18 ], German [ 18 ], Greek [ 19 ], Italian [ 20 , 21 ], Spanish [ 14 ], Thai [ 22 ] and Luganda [ 23 ].…”
Section: Introductionmentioning
confidence: 99%